Emerging malaria in Indonesia: An overview of Plasmodium knowlesi infections - Nisa Fauziah; Karomahul Malaya Jati; Fedri Ruluwedrata Rinawan; Naufal Fakhri Nugraha; Bachti Alisjahbana; Jontari Hutagalung (Parasite Epidemiology and Control)
Background: Plasmodium knowlesi, the fifth malaria-causing parasite species, is currently changing the landscape of the most dominant malaria-causing species in the Southeast Asia by becoming the emerging significant cause of malaria in the region, including in Indonesia. This study aimed to provide an overview of malaria caused by P. knowlesi in Indonesia. Methods: This study utilized secondary data from the Indonesian National Referral Malaria Laboratory from 2011 to 2020 for the analysis. Results: Analysis on 212 samples collected over ten years identified 66 (31.1 %) cases of P. knowlesi infection, with one (0.5 %) mixed infection of P. knowlesi and P. vivax. These cases were reported in seven provinces in Kalimantan and Sumatra islands. Males were 2.23 times more likely to be at risk for malaria compared to females, and this result was statistically significant (p-value = 0.037, 95 % CI: 0.84–5.91). There was no significant association between the risk of malaria and the age groups classified as non-productive and productive (p-value = 0.535, OR = 0.42, 95 % CI: 0.12–1.53). Individuals working outdoors were not significantly more protected compared to those working indoors (p-value of 0.116, OR = 0.15, 95 % CI: 0.02–1.49). The origin of the sample was found to be the most significant factor (p-value <0.001), with individuals from Kalimantan having the highest risk for malaria caused by P. knowlesi (OR = 3.97, 95 % CI: 2.10–7.49). Conclusions: Two major Indonesian islands of Sumatra and Kalimantan, which reported malaria cases during the period studied, exhibit a potential risk for P. knowlesi infections that is influenced by factors beyond natural hosts and vectors, such as sex, age, and occupation. Routine PCR examinations for suspected P. knowlesi infections are crucial for developing effective strategies to identify and control this simian malaria parasite.